Disabling Domesticity - Rembis, Michael (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2017)
Bringing together a range of authors from the multidisciplinary field of disability studies, this book uses disability and the experiences of disabled people living in the United States and Canada to explore and analyze dynamic sites of human interaction in both historical and contemporary contexts to provide readers with new ways of envisioning home, care, and family. Contributors to Disabling Domesticity focus on the varied domestic sites where intimate - and interdependent - human relations are formed and maintained. Analyzing domesticity through the lens of disability forces readers to think in new ways about family and household forms, care work, an ethic of care, reproductive labor, gendered and generational conflicts and cooperation, ageing, dependence, and local and global economies and political systems, in part by bringing the notion of interdependence, which undergirds all of the chapters in this book, into the foreground.- Resumé vydavatel